2015
DOI: 10.1111/efp.12185
|View full text |Cite
|
Sign up to set email alerts
|

Local population structure of Hymenoscyphus fraxineus surveyed by an enlarged set of microsatellite markers

Abstract: Summary The population structure of Hymenoscyphus fraxineus, the causal agent of ash dieback, was assessed at four closely located sites in the Czech Republic. To analyse the genetic variation, one Swiss and one Norwegian population with known population structures were selected as reference points. The analysis was performed using 16 previously published and five newly developed microsatellite markers. The quality of the new markers was assessed by sequencing the flanking region, identifying the type of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Since ash dieback was observed in the Czech Republic since late 1990's and detected in 2007 [22] the disease has spread over forests, plantations, urban areas, and nurseries throughout the country [23]. However, no biological studies about the causal agent of ash dieback had been carried out in our country so far.…”
Section: Detection Of Air-inoculummentioning
confidence: 99%
See 1 more Smart Citation
“…Since ash dieback was observed in the Czech Republic since late 1990's and detected in 2007 [22] the disease has spread over forests, plantations, urban areas, and nurseries throughout the country [23]. However, no biological studies about the causal agent of ash dieback had been carried out in our country so far.…”
Section: Detection Of Air-inoculummentioning
confidence: 99%
“…Since then, the disease has been increasingly observed in a number of areas with different severity [23]. Therefore, the aims of this study were (i) to thoroughly describe the seasonal pattern of H. fraxineus and H. albidus ascospores dispersal in the locality where the ash dieback was firstly described in our country; (ii) to determine the influence of meteorological conditions on its biology; and (iii) to compare efficiency of rotating arm spore trap and seven-day automatic volumetric spore trap together with evaluation of the samples by qPCR.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of genetic diversity of H. fraxineus in Europe using SSR markers have indicated that European isolates come from the same source population and that differentiation between subpopulations is small, allelic variation is low and genotypic diversity is high (Gross et al ., ; Burokiene et al ., ; Haňáčková et al ., ). The only study of phenotypic variation to date reported diversity in vegetative compatibility (VC) types, a system that defines genetic individuals within a fungal population (Brasier & Webber, ).…”
Section: Introductionmentioning
confidence: 99%
“…H. fraxineus was isolated from shoot segments in the proximal direction from each leaf scar and from the two-yearold shoot in cases of apparent necrosis, according to Haňáčková et al (2015). H. fraxineus was isolated from shoot segments in the proximal direction from each leaf scar and from the two-yearold shoot in cases of apparent necrosis, according to Haňáčková et al (2015).…”
Section: Isolation Of Hymenoscyphus Fraxineus and Dna Extractionmentioning
confidence: 99%
“…Dead and fresh leaf petioles are colonized by multiple genotypes of the same fungal species (Gross, Zaffarano, Duo & Grünig, 2012;Hayatgheibi, 2013;Nguyen, Cleary, Enderle, Berlin, & Stenlid, 2016), and even an individual necrotic bark lesion may contain more than one genotype of H. fraxineus, as recorded by Bengtsson, Barklund, von Brömssen, and Stenlid (2014) and Haňáčková, Koukol, Havrdová, and Gross (2015). Dead and fresh leaf petioles are colonized by multiple genotypes of the same fungal species (Gross, Zaffarano, Duo & Grünig, 2012;Hayatgheibi, 2013;Nguyen, Cleary, Enderle, Berlin, & Stenlid, 2016), and even an individual necrotic bark lesion may contain more than one genotype of H. fraxineus, as recorded by Bengtsson, Barklund, von Brömssen, and Stenlid (2014) and Haňáčková, Koukol, Havrdová, and Gross (2015).…”
Section: Introductionmentioning
confidence: 99%